The Effect of Malrotation of Tibial Component of Total Knee Arthroplasty on Tibial Insert during High Flexion Using a Finite Element Analysis - Kei Osano; Ryuji Nagamine; Mitsugu Todo; Makoto Kawasaki (The Scientific World Journal)
One of the most common errors of total knee arthroplasty procedure is a malrotation of tibial component. The stress on tibial insert is closely related to polyethylene failure. The objective of this study is to analyze the effect of malrotation of tibial component for the stress on tibial insert during high flexion using a finite element analysis. We used Stryker NRG PS for analysis. Three different initial conditions of tibial component including normal, 15° internal malrotation, and 15° external malrotation were analyzed. The tibial insert made from ultra-high-molecular-weight polyethylene was assumed to be elastic-plastic while femoral and tibial metal components were assumed to be rigid. Four nonlinear springs attached to tibial component represented soft tissues around the knee. Vertical load was applied to femoral component which rotated from 0° to 135° while horizontal load along the anterior posterior axis was applied to tibial component during flexion. Maximum equivalent stresses on the surface were analyzed. Internal malrotation caused the highest stress which arose up to 160% of normal position. External malrotation also caused higher stress. Implanting prosthesis in correct position is important for reducing the risk of abnormal wear and failure.